Antagonistics Affinities: Cunqueiro, Translator of the "Beat Generation" - Costas, Xosé-Henrique (Madrygal. Revista de Estudios Gallegos, 2018)
Between 1970 and 1978 Álvaro Cunqueiro was publishing poetic translations of Beat Generation in the literary pages of the Faro de Vigo. He translated eight poems from Corso, Ferlinghetti, Ginsberg and Kerouac among the more than 300 authors translated into Galician language by the author in this newspaper between 1965 and 1981. The translations of beat poets are astonishing because it is a priori a movement far away from the poetic sensibility of Cunqueiro. However, it is shown that no poetry was strange to Cunqueiro, very attentive to all literary novels and eager to extend –with its translations into our language– the symbolic capital of the Galician literary field. We will show the translations together with the original verses and, in addition, we will analyze if this poetic antagonism is total or if there are affinities between the poetic beat and the poetics of Álvaro Cunqueiro.